ANALISIS BIAYA PENGEMBANGAN JARINGAN TRANSMISI UPT JEMBER UNTUK MENGANTISIPASI PERTUMBUHAN BEBAN - Saleh, Azmi (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2011)
Transmission line needs to make expansion planning to anticipate the load growing every year to avoid over load or bad voltage profile (out the voltage tolerance above 0,95 pu -1,05 pu from base voltage). The analysis of expansion planning is use simulation with PSAT software with assume load growing 10 % every years from preview year. If the line current in transmission has over load, the expansion planning that have to do is adding the line capacity or replacing line cable type. If the voltage profile has badly, the expansion planning that have to do is adding the STATCOM to bus that have problem. The result of analysis the expansion planning of transmission line in UPT Jember for duration 10 years are expansion planning of transmission line in fourth, fifth, eight and tenth years. In ten years also need to adding the STATCOM in Tanggul substation. The estimation of total infestations to cover load growing during 10 years is $3.458.018.86.